Factoring in Factor VIII With Acute Ischemic Stroke - Siegler, James E. (Clin Appl Thromb Hemost, 2015)
There is growing research interest into the etiologies of cryptogenic stroke, in particular as it relates to hypercoagulable states. An elevation in serum levels of the procoagulant factor VIII is recognized as one such culprit of occult cerebral infarctions. It is the objective of the present review to summarize the molecular role of factor VIII in thrombogenesis and its clinical use in the diagnosis and prognosis of acute ischemic stroke. We also discuss the utility of screening for serum factor VIII levels among patients at risk for, or those who have experienced, ischemic stroke.